PUBLIC GOVERNANCE DAN KORUPSI: BUKTI PENGUJIAN DARI INDONESIA MENGGUNAKAN PERSPEKTIF TEORI KEAGENAN - Evi Maria; Abdul Halim (UNIB Press, 2021)
This article explores public governance impact on the corruption’s probability in Indonesian local government practices. The research employs data of Indonesian local governments in 2012. Data were analyzed using logistic regression. The study results found that good public governance has a negative effect on corruptio’s probability. The results of this research conclude that the greater public governance index, the less the local government’s engagement in corruption. The results are rugged when area type is added as control variable. Area type do not affect the corruption’s probability in Indonesian local governments. This study found good public governance decreases the asymmetry of information between agents and principals, so that the opportunity to commit corruption are reduced. Improvement of public governance can be done by implementing e-Government to supervise the implementation of government activities and public services in local government, Indonesia.